Family Background and the Responses to Higher SAT Scores - Georg Graetz; Björn Öckert; Oskar Nordström Skans (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Using discontinuities within the Swedish SAT system, we show that additional admission opportunities causally affect college choices. Students with high-educated parents change timing, colleges, and fields in ways that appear consistent with basic economic theory. In contrast, very talented students with low-educated parents react to higher scores by increasing overall enrolment and graduation rates. Remarkably, most of this effect arises from increased participation in college programs and institutions that they could have attended even with a lower score. This suggests that students with low-educated parents face behavioral barriers even in a setting where colleges are tuition-free, student grants are universal and application systems are simple.
Keywords: I21; I23; J62; 330; educational choice; intergenerational transmission of education; regression discontinuity design